The new lesbian studies: Into the twenty-first century - Zimmerman, Bonnie; McNaron, Toni A. H. (Feminist Press at the City University of New York, 1996)
Foreword by Margaret Cruikshank Introduction by Bonnie Zimmerman and Toni A. H. McNaron By celebrating the differences among lesbian scholars and attending to the ways in which the field has been shaped by shifting politics and the emergence of queer studies, this collection challenges the limits of lesbian studies while affirming its value. Forty essays arranged in six parts explore the history of lesbian studies as well as its current impact on conceptions of identity and community, teaching, academic disciplines, university practices, and the development of feminist and queer theories. The collection offers stirring personal testimony; multicultural and international perspectives and established and new voices; strategies for integrating lesbian studies into the curriculum; and contributions from lesbians working in libraries, athletic departments, and students services. Throughout, the contributors address the ways in which lesbian studies has transformed and will continue to transform traditional disciplines, practices, and thought.
Keywords: approches et analyses; histoire et politique; lesbianisme; personnes lesbiennes; queer; thématiques